Activite Antifongique Des Flavonoïdes Isoles De La Plante Asteriscus Graveolens Subsp. Odorus (Schousb.) Greuter - Alilou, Hakim; Bencharki, Bouchaib; Talbi, Jalal; Barka, Noureddine (European Scientific Journal, ESJ, 2016)
A phenol acid and three flavones isolated from the plant Asteriscus graveolens subsp. odorus were tested against three fungi: Botrytis cinerea, Penicillium digitatum and Penicillium expansum. Using the method of incorporation of products in a PDA, a high sensitivity of Botrytis cinerea to caffeic acid and nevadensine was observed. Penicillium digitatum is the sensitive to luteolin, as to Penicillium expansum, it marks a sensitivity to artemetin. The efficacy of the tested molecules could be the subject of an investigation and exploitation in the integrated fight against the three tested fungi that cause a lot of damage to fruits and vegetables post-harvest.